(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Climate change is affecting the livelihoods of people living in the mountainous regions of Kyrgyzstan. Water is becoming a scarce resource, especially during the spring and summer months when agricultural activity is at its peak. People are compelled to find ways to compensate for the shortage. This article explores an innovative method for water conservation in Kyrgyzstan, the creation of artificial glaciers. Based on empirical data, field case studies, and interviews, the article describes the glacier-making technology, its technical features, the social engagement of local communities, funding mechanisms, and the role of international organizations. Drawing on the experience of constructing 11 artificial glaciers, the article presents ecological and social impacts, such as improved vegetation on pastures and better grazing conditions, increased water availability, mobilization of local communities. The article highlights the need for further scientific research to evaluate the effectiveness and scalability of this technology. It lays a practical foundation for interdisciplinary understanding of climate-adaptive solutions in the mountain regions of Central Asia.